Penerapan Format Baru Pendokumentasian Asuhan Keperawatan Di Poli Rawat Jalan Puskesmas - Pius Kopong Tokan; Maria Salestina Sekunda (Poltekkes Kemenkes Kupang, 2020)
Background: Average patient visits in outpatient polyclinics at Rukun lima Health Center in 2018 is & 80-100 people per day. However the process of nursing care documentation is not carried out. according to the provisions of efforts that have been made is to renew the format of God nursing base do local conditions In connection with that it need stobe done for know the description of the application of the new format in the process of documenting nursing care outpatient care clinic Rukun lima. Method: Survey research is descriptive, research variables in the formof documentation on the process with the study of diagnoses, interventions, implementation, andevacuation of nursing. The research was conducted in thepublic roli roomatthe Puskesmas Rukun Lima from July September 2019. Anticipate drop out. Data collected by observation and interview sheets. Descriptive data processing in the form of proportions and the subsequent average univariant analysis. Results: Documenting nursing assessment 5%. 21% nursing diagnoses, 12% nursing interventions, nursing implementation 26%. Conclusion: The application of the new format for documenting nursing care in outpatient care. The Rukun lima Community Health Center is classified as poor because it is incomplete 36 of the target of atleast 60%. At the nursing assessment stage only reaches 5% of diagnos nursing only reaches 21% nursing planning only reaches 12%, action nursing only reaches 26%. Where as nursing evaluation is not carried out because the patient's status is out patient. Latar belakang: Rata-rata kunjungan pasien di poli rawat jalan Puskesmas Rukunlima tahun 2018 adalah 80-100 orang per hari. Namun demikian proses pendokumentasian asuhan keperawatan tidak dilakukan sesuai ketentuan. Sehubungan dengan itu perlu dilakukan pengkajian untuk mengetahui gambaran penerapan format baru dalam proses pendokumentasian asuhan keperawatan di poli rawat jalan Puskesmas Rukunlima. Metode: penelitian survey bersifat deskriptif, variabel penelitian berupa dokumentasi pada proses pengkajian, diagnosa, intervensi, implementasi, dan evaluasi keperawatan. Penelitian dilaksanakan di ruang roli umum Puskesmas Rukun Lima dari bulan Juli - September 2019. Populasi dalam penelitian ini adalah berkas dokumen asuhan keperawatan dari bulan Januari-Juni 2019 dengan metoda sampling adalah estimasi proporsi ditambah 10% untuk antisipasi drop out. Data dikumpulkan dengan lembar observasi dan wawancara. Pengolahan data:secara deskriptif berupa proporsi dan rata-rata selanjutnya dilakukan analisis univariant. Hasil: Pendokumentasian pengkajian keperawatan 5%, diagnosa keperawatan 21%, intervensi keperawatan 12%, implementasi keperawatan 26%. Kesimpulan: Penerapan format baru untuk pendokumentasian asuhan keperawatan di poli rawat jalan Puskesmas Rukunlima dikategorikan kurang baik karena tidak lengkap dan jumlah rata-ratapengisian dokumen masih jauh dibawah nilai standar.